Synthesis of Thermally Stable Polyamide Phosphonicdihydrazides - Shukla, J.S.; G.H. Zaidi, Mohd.; Dixit, S.K. (Asian Journal of Chemistry, 2010)
The low temperature solution polycondensation of bis(3-amino-benzoylhydrazino) phosphite with different aromatic diacid chlorides in N,N-dimethylacetamide at –10ºC afforded the fusible and soluble polyamides having inherent viscosity in the range of 0.08–0.17 dL g–1. Isothermal weight loss analysis in air revealed that all the polyamides were stable upto 300ºC.